Toshihiko Izutsu's Semantics on the Multicultural Education of the Qur'an in Arabic Language Learning - Nasarudin, Nasarudin; Mustaufiy, Ahmad Syagif Hannany; Khotimahis, Isnol; Rauhillah, Siti; Sari, Alvia Putri Prima; Sardi, Janudin (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study aims to analyze Qur’anic verses for multicultural values using Toshihiko Izutsu’s semantic approach and to present pedagogical illustrations, informed by student reflections, that show how semantic awareness may emerge in Arabic language learning contexts. The study adopts a conceptual–qualitative research design that emphasizes textual interpretation and pedagogical reflection rather than the empirical evaluation of instructional effectiveness. Conceptual semantic analysis based on Izutsu’s framework is applied to selected Qur’anic verses through four interrelated layers of meaning: basic meaning, relational meaning, historical meaning, and worldview (Weltanschauung). The analysis demonstrates that multicultural values, such as diversity, justice, dialogue, social cooperation, and recognition of religious plurality, are constructed through relational networks of meaning linking key concepts, syntactic structures, and discourse patterns. Pedagogical illustrations drawn from reflective student accounts suggest that semantic-oriented engagement with Qur’anic texts can foster contextual, relational, and ethical awareness in Arabic language learning.